Adsorption properties of a paracyclophane molecule on NaCl/Au surfaces: a first-principles study. Issue 8 (8th February 2023) - Xiao, Jiyin; Zhao, Wenjing; Li, Li; Ma, Liang; Tian, Guangjun
Abstract : Theoretical simulation indicates that three layers of insulating NaCl layers is sufficient to decouple a double-decker 3, 3-paracyclophane molecule from Au(111) surface to preserve the intrinsic properties of the molecule. Abstract : Ultrathin insulating layers are commonly applied in scanning tunneling microscope (STM) measurements on molecular systems to preserve the intrinsic properties of a sample. We examine in the present work the adsorption properties of a double-decker 3, 3-paracyclophane (PCP) molecule supported on Au surfaces with thin NaCl monolayers (MLs) as the decoupling spacer by using first-principles calculations. The interactions between the adsorbed molecule and the substrate were analyzed in terms of the adsorption energy, dispersion interactions, charge transfer, and molecular structure changes. The simulation results show that the presence of NaCl can significantly reduce the adsorption energy as well as the charge transfer between the molecule and the substrate. Detailed analysis of the differential charge density and partial charge density of states indicates that three MLs of NaCl are sufficient to decouple the molecule from the Au substrate with no significant changes in the adsorption properties of the PCP with the further increase of the thickness of the NaCl spacer. These results could be helpful for the application of the interesting double-decker molecules as functional single-molecule devices where the intrinsic molecular properties need to be preserved.